Structural evaluation and analysis of existing house renovation into shophouse based on Building Information Modeling - Ahmad Yudi; Nugraha Bintang Wirawan; Siti Rahma; Kartinanda P.; Amantawidya Durratul Hikmah; Annida Evilia Miranda; Siska Apriwelni (Teknisia, 2024)
Indonesia's population and economic growth must be supported by adequate facilities and infrastructure, including residences and business premises. Renovating residential houses into shophouses offers an effective way to optimize land use and reduce construction costs. A thorough evaluation of existing structural elements is critical to determining which components can be retained, alongside accurate cost and scheduling assessments to ensure smooth renovation. This research utilizes Building Information Modeling (BIM) to integrate structural, architectural, and MEP work, as well as to streamline scheduling and cost estimation. ETABS is employed for structural design, while Autodesk Revit and Navisworks are used for cost and schedule planning. The assessment follows ASCE 41-17 guidelines to evaluate existing structures, and SNI 1726:2019 and SNI 2847:2019 standards for retrofitting and designing new structures. The evaluation reveals deficiencies in global strength and component ductility, necessitating structural retrofits using concrete jacketing. This study not only addresses the renovation of a residential house into a shophouse but also contributes to broader research in construction. The estimated cost for the structural renovation is Rp. 159,692,607.93, and the duration is projected at 58 days, with 11 days for demolition and 47 days for upper structure construction.